2007
DOI: 10.1186/1471-2164-8-341
|View full text |Cite
|
Sign up to set email alerts
|

Collembase: a repository for springtail genomics and soil quality assessment

Abstract: Background: Environmental quality assessment is traditionally based on responses of reproduction and survival of indicator organisms. For soil assessment the springtail Folsomia candida (Collembola) is an accepted standard test organism. We argue that environmental quality assessment using gene expression profiles of indicator organisms exposed to test substrates is more sensitive, more toxicant specific and significantly faster than current risk assessment methods. To apply this species as a genomic model for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 43 publications
3
55
0
Order By: Relevance
“…The F. candida strain used in our study may be infected by RLO as well. Bioinformatic analysis of a recently published EST dataset of the same strain (Timmermans et al 2007) revealed two sequences (GenBank: EV480534 and GE647879) which each harbored a fragment that showed high similarity to the published RLO sequence. Still, in our experiments with F. candida we can be reasonably sure that the effect of rifampicin and heat treatment can be attributed to Wolbachia, because these RLO seem to be restricted to the gut and the fatbody of F. candida (they are not associated with gonads (Czarnetzki and Tebbe 2004a)).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The F. candida strain used in our study may be infected by RLO as well. Bioinformatic analysis of a recently published EST dataset of the same strain (Timmermans et al 2007) revealed two sequences (GenBank: EV480534 and GE647879) which each harbored a fragment that showed high similarity to the published RLO sequence. Still, in our experiments with F. candida we can be reasonably sure that the effect of rifampicin and heat treatment can be attributed to Wolbachia, because these RLO seem to be restricted to the gut and the fatbody of F. candida (they are not associated with gonads (Czarnetzki and Tebbe 2004a)).…”
Section: Discussionmentioning
confidence: 98%
“…However, the recent establishment of an EST database for F. candida (Timmermans et al 2007) will greatly facilitate a more detailed molecular analysis of the genetic changes produced by Wolbachia infection.…”
Section: Discussionmentioning
confidence: 99%
“…cDNA was synthesized from 1μg total RNA using the Omniscript Reverse Transcriptase Kit (Qiagen) and an Anchored Oligo(dT)20 primer (Invitrogen A/S, Naerum, Denmark) in a total volume of 13μl according to the manufacturer's instructions. Sequences for genes analysed were obtained from http://www.collembase.org (Timmermans et al, 2007). Primers were designed using Primer3 (Rozen and Skaletsky, 2000) and synthesized by MWG Eurofins (Ebersberg, Germany; Table1).…”
Section: Gene Expressionmentioning
confidence: 99%
“…The first strand cDNA was synthesized using reverse transcriptase MMLV (Promega) and oligod(T) 15 according to the manufacturer's instructions. The b-actin gene was chosen as an internal control for hsp70 gene quantification (Timmermans et al 2007). The two genes were quantified by SYBR Green I assays using the primer set ACT1-F (GCGACGTTGAT ATCCGAAAG) and ACT1-R (AGGCAGTGATTTCCTT TTGC) for b-actin gene, and the primer set H7-1F (GG ACTTTGACAACCGAATGG) and H7-1R (CCACGGA AAAGATCAGCATT) for hsp70 gene.…”
Section: Transcriptional Responses Of Hsp70 In F Candidamentioning
confidence: 99%